2022
DOI: 10.1002/cssc.202102379
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Electrochemical Oxygen Reduction Performance of Iron Phthalocyanine through Axial Coordination Sphere Interaction

Abstract: Precise regulation of the electronic states of catalytic sites through molecular engineering is highly desired to boost catalytic performance. Herein, a facile strategy was developed to synthesize efficient oxygen reduction reaction (ORR) catalysts, based on mononuclear iron phthalocyanine supported on commercially available multi‐walled carbon nanotubes that contain electron‐donating functional groups (FePc/CNT‐R, with “R” being −NH2, −OH, or −COOH). These functional groups acted as axial ligands that coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…24 25−27 In another study, Zhang et al reported molecular iron phthalocyanine supported on functionalized multiwalled carbon nanotubes (CNTs) and obtained an N−Fe−N 4 site with the axial N atom coordinated to the FeN 4 and CNTs, yielding enhanced ORR performance in comparison to the nonfunctionalized FePc/CNT and stateof-the-art Pt/C catalyst. 28 Several theoretical studies have suggested that the activity of Fe−N 4 SACs is restricted by the strong binding of reaction intermediate (e.g., OH*) on the single Fe site, and the introduction of an axial coordination effect can decrease the orbital hybridization of Fe active center with ORR intermediates, leading to accelerated ORR activity. 29−32 It is worth noting that most of the current theoretical understanding of the ORR activity was based on the charge-neutral model (CNM), which keeps constant charge and neglects the surface charge effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24 25−27 In another study, Zhang et al reported molecular iron phthalocyanine supported on functionalized multiwalled carbon nanotubes (CNTs) and obtained an N−Fe−N 4 site with the axial N atom coordinated to the FeN 4 and CNTs, yielding enhanced ORR performance in comparison to the nonfunctionalized FePc/CNT and stateof-the-art Pt/C catalyst. 28 Several theoretical studies have suggested that the activity of Fe−N 4 SACs is restricted by the strong binding of reaction intermediate (e.g., OH*) on the single Fe site, and the introduction of an axial coordination effect can decrease the orbital hybridization of Fe active center with ORR intermediates, leading to accelerated ORR activity. 29−32 It is worth noting that most of the current theoretical understanding of the ORR activity was based on the charge-neutral model (CNM), which keeps constant charge and neglects the surface charge effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This work explored the axial coordination effect of different electron donating groups on the Fe center of FePc. The −NH 2 axial ligand is the most electron‐donating, which endowed the FePc with the highest ORR activity, including a positive onset potential of 1.0 V versus RHE and a half‐wave potential ( E 1/2 ) of 0.92 V versus RHE [31] . DFT study evidenced that the electron‐donating ligands could facilitate the adsorption and activation of O 2 .…”
Section: Axial Coordination Modification Of Sacsmentioning
confidence: 97%
“…The À NH 2 axial ligand is the most electron-donating, which endowed the FePc with the highest ORR activity, including a positive onset potential of 1.0 V versus RHE and a half-wave potential (E 1/2 ) of 0.92 V versus RHE. [31] DFT study evidenced that the electrondonating ligands could facilitate the adsorption and activation of O 2 . Inspired by the biosystems, Liu and co-workers designed an ORR electrocatalyst by covalently attaching an axial imidazolecoordinated porphyrin to MWCNTs.…”
Section: N-containing Ligandsmentioning
confidence: 99%
See 2 more Smart Citations